Peran Layanan Jasa Search Engine Optimization untuk Meningkatkan Daya Saing pada Bisnis Startup (Studi pada Kaldera Trail and Jeep Adventure Malang) - Wira Bharata (Al Tijarah, 2016)
This study aimed to investigate the role of SEO as a strategic competitive advantage. This study uses a qualitative approach with case studies are used as a research design. Researchers in the interviews to the owner Caldera Trail & Jeep Adventure. The results of this study indicate that the role of SEO to optimize the website proved successful in the company’s competitive advantage strategy Caldera Trail & Jeep Adventure. The results showed online marketing is done through Facebook, Twitter, Instagram and website have a positive impact on sales in their services. Applying marketing strategies using social media-based social networks and websites are very efficient because of much greater use conventional marketing strategies. This study also emphasizes the social media as online advertising that can be used as a marketing strategy in today’s digital era.